Using Wiki in teacher education: Impact on knowledge management processes and student satisfaction - Biasutti, Michele; EL-Deghaidy, Heba (Computers and education, 2012)
The current study reports on the use of Wiki as an online didactic tool to develop knowledge management (KM) processes in higher education. This study integrates social constructivist principles to learning where learners are pro-active and collaborative through higher order cognitive processes. The study was administered in two countries, namely Egypt and Italy, to close a gap in the literature with an aim to introduce KM processes in teacher educational programmes. These processes are seen as necessary for teachers’ professional skills. Such processes are claimed to enable teachers and therefore schools to evolve in a networked information-driven global society, especially as the complexity of subject knowledge is increasing. It is also a learning experience where teachers learn how to provide their students with educational settings where technology is enabled. Throughout the study, 27 Egyptian students and 36 Italian students participated in online activities and developed interdisciplinary projects for the primary and preparatory stages while collaborating in a Wiki experience within Moodle platform. The study followed a mixed methods approach that consisted of both quantitative and qualitative data. The authors developed several instruments in order to measure both processes and outcomes of the five-week online activities. This current study is reporting on the use of two closed question instruments and one open question instrument. These were: Knowledge Management Questionnaire (KMQ), Student Satisfaction Questionnaire (SSQ) and a Reflection Questionnaire (RQ). Data were analysed using statistical analysis and inductive content analysis. Results indicate that responses on the KMQ were all reliable >0.70, and fulfilled the five processes of KM and participants were highly satisfied. The results suggest that Wikis can develop teachers’ knowledge management processes and fulfil student’s satisfaction while collaborating in designing interdisciplinary projects. Future implications and suggestions for teacher education programmes are provided in light of the findings. ► We examined the use of Wikis as an online didactic tool. ► We used socio-constructivist theory as the study’s framework. ► Results showed that Wikis developed teachers’ knowledge management processes. ► Students were satisfied with the online Wiki activities. ► Professor and participants’ role changed dramatically during the online activities.